Temporal discrete Z-number and its application in assessing EEG signal data of epileptic seizure - Abdullahi, Mujahid; Tahir Ahmad,; Vinod Ramachandran, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Analysis and modeling of a complex physical system, particularly EEG signals involved vague and uncertain information. The approach introduced by Kosanovic using temporal fuzzy set to model a complex system particularly the EEG signal does not address the problem of uncertainty for the time of occurrence. In this paper, an ordered discrete Z-number is used to construct temporal discrete Z-number to assess EEG signal data of an epileptic seizure for the first time. The proposed temporal discrete Z-number is able to accommodate the problem of uncertainty with regards to the time of occurrence for a given seizure by using and modifying the method for measuring the uncertainty of Z-number.